Astronomical pacing of Late Cretaceous third- and second-order sea-level sequences in the Foz do Amazonas Basin. (July 2020) - Boulila, Slah; Brange, Célia; Cruz, Alberto Machado; Laskar, Jacques; Gorini, Christian; Reis, Tadeu Dos; Silva, Cleverson Guizan
Abstract: Because of their relatively reduced tectonic influence, post-rift sedimentary successions have a propensity to preserve climatically-driven cyclicity over long durations. Here we present an integrated cyclostratigraphic and sequence stratigraphic study of the post-rift Limoeiro sedimentary Formation (Fm) of the Foz do Amazonas Basin (offshore Brazil), which spans the entire Late Cretaceous epoch (almost 35 Myr long). The principal goal of the present study is to decipher very long (multi-Myr) sedimentary cyclicities and their potential origin(s) in order to delineate the main controlling factors of post-rift sediment sequences and packages. We used gamma-ray (GR) well-log data for cyclostratigarphy, and seismic data for sequence stratigraphy. Time-series analysis of GR data shows a rich series of Milankovitch frequency bands. In particular, long-period cyclicities (405 kyr, 2.4 Myr, 4.7 Myr and 9.5 Myr) are detected with high fidelity. Seismic and sequence stratigraphic interpretation shows a striking sea-level (SL) depositional sequence order, matching the 4.7 Myr orbital cyclicity inferred from cyclostratigraphy. Longer SL sequences interpreted in previous studies from the Limoeiro Fm closely match the 9.5 Myr GR related orbital cycles. Thus, we infer that the post-rift Limoeiro Fm was deposited continuously under astronomical forcing over the Late Cretaceous epoch, resulting in an extraordinary record of direct base- and sea-level responses to Milankovitch climatic forcing, including longer (multi-Myr) periodicities. The 4.7 Myr orbital component is recorded for the first time in SL sedimentary proxies, thus allowing here to update SL hierarchical orders. We suggest that third-order, and second-order and suborders SL sequences were most likely paced by long-period astronomical cycles (2.4 Myr eccentricity, and 4.7 and 9.5 Myr orbital cycles, respectively. Highlights: An integrated cyclo-seismic stratigraphy detects 2.4, 4.7 and 9.5 Myr orbital cycles. 2.4, 4.7 and 9.5 Myr orbital cycles match third and second-order sea-level sequences. The 4.7 Myr orbital cycle is highlighted for the first time in sea-level record.